Resistance to Benzimidazoles in Haemonchus, Trichostrongylus and Strongyloides species in Sheep Farms of Three Agro-Climatic Zones of Haryana, India - Kalkal, Hardeep; Ravinder; Yadav, Nisha; Lal, Madan; Vohra, Sukhdeep; Kumar, Sunil; Kumar, Narender; Rajput, Vinita (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The regular and frequent use of similar anthelmintics has led to the development and prevalence of anthelmintic resistance which hinders the control of gastrointestinal nematodes (GINs) in sheep. The present research work was planned with the aim of studying the status of benzimidazole group of drug to GINs in sheep farms (one organized and 3 unorganized) of arid (Zone-I, Hisar), semi-arid (Zone-II, Kaithal) and dry sub-humid (Zone-III, Ambala) Zones of Haryana, India using in vivo faecal egg count reduction test (FECRT) and in vitro egg hatch assay (EHA). The FECRT resulted moderate resistance (60.60-75.26%) in all the selected sheep farms against fenbendazole @ 5 mg/kg b.wt. orally. The faecal culture revealed the predominance of H. contortus infective larvae with few Trichostrongylus spp. and Strongyloides spp. However, EHA revealed resistance in two farms (0.108-0.110 µg TBZ/mL) and susceptibility (0.087-0.092 µg TBZ/mL) of other two farms to thiabendazole, i.e., there ED50 values were below 0.1 µg TBZ/mL. This seems to be the first study of anthelmintic resistance against GINs in sheep farms from three agro-climatic zones of Haryana. This basic knowledge on resistance of benzimidazoles group of drug will help in formulating a strategy to control gastrointestinal nematodes in sheep of Haryana.